Quality of Life, Toxicity and Unmet Needs in Nasopharyngeal Cancer Survivors - McDowell, Lachlan; Corry, June; Ringash, Jolie; Rischin, Danny (Frontiers in Oncology, 2020)
Concerted research efforts over the last three decades have resulted in improved survival and outcomes for patients diagnosed with nasopharyngeal carcinoma (NPC). The evolution of radiotherapy techniques has facilitated improved dose delivery to target volumes while reducing dose to the surrounding normal tissue, improving both disease control and quality of life (QoL). In parallel, clinical trials focusing on determining the optimal systemic therapy to use in conjunction with radiotherapy have been largely successful, resulting in improved locoregional, and distant control. As a consequence, neoadjuvant chemotherapy (NACT) prior to definitive chemoradiotherapy has recently emerged as the preferred standard for patients with locally advanced NPC. Two of the major challenges in interpreting toxicity and QoL data from the published literature have been the reliance on: (1) clinician rather than patient reported outcomes; and (2) reporting statistical rather than clinical meaningful differences in measures. Despite the lower rates of toxicity that have been achieved with highly conformal radiotherapy techniques, survivors remain at moderate risk of persistent and long-lasting treatment effects, and the development of late radiation toxicities such as hearing loss, cranial neuropathies and cognitive impairment many years after successful treatment can herald a significant decline in QoL. Future approaches to reduce long-term toxicity will rely on: (1) identifying individual patients most likely to benefit from NACT; (2) development of response-adapted radiation strategies following NACT; and (3) anticipated further dose reductions to organs at risk with proton and particle therapy. With increasing numbers of survivors, many in the prime of their adult life, research to identify, and strategies to address the unmet needs of NPC survivors are required. This contemporary review will summarize our current knowledge of long-term toxicity, QoL and unmet needs of this survivorship group.